The Correlation between Self-efficacy and Motivation on Elderly's Daily Independence - Anggita Febriana; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2024)
Background: Changes in body composition during adolescence can affect the self-concept of teenagers, including self-esteem and body image. Physical changes often drive teenagers to strive for an ideal appearance through various means, including make-up. Adolescents preoccupied with physical appearance tend to develop opinions and feelings about their bodies' size, shape, appearance, and abilities. This study aimed to determine the correlations between make-up dependency to self-esteem and body image among female students in the Faculty of Health Sciences at Universitas Muhammadiyah Purwokerto. Method: This study utilized a quantitative descriptive approach involving 180 female students aged 18-22, selected through random sampling. Data was collected using DeFleur's makeup dependency questionnaire, the Rosenberg Self-Esteem Scale (RSES), and the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS). Statistical data analysis was performed using the Chi-square test (X2). Results: The results revealed that the majority of the female students; obtained a moderate level of makeup dependency, had high self-esteem, showed a positive body image, there was no significant correlation between makeup dependency and self-esteem, with a p-value of 0.764 > 0.05, and there was no significant correlation between makeup dependency and body image, with a p-value of 0.063 > 0.05. Conclusion: Both self-esteem and body image are high and positive among female students.